Evaluation of dry sliding wear behavior of abaca/glass fiber hybrid composite for tribological applications. (March 2023) - Prakash, Ved; Pradhan, Subhrajit; Majhi, Sudhakar; Acharya, Samir Kumar
Abaca is a high-strength natural fiber whose tribological behavior in epoxy polymer composite is unexplored to date. This paper aims to study the mechanical and dry sliding wear behavior of abaca fiber (A) and glass fiber (G) reinforced epoxy laminate composites with various stacking sequences. Symmetrically oriented laminate composites were fabricated in different stacking sequences (AAAA, AGAG, AGGA, and GAAG) using hand lay-up technique. Mechanical characterization is carried out as per ASTM standards. It is found that GAAG hybrid composite possesses maximum tensile strength (101.05 MPa). Meanwhile, AGAG composite shows maximum flexural strength (190.15 MPa) and interlaminar shear strength (5.97 MPa). Abrasive wear behavior of the composites is investigated by performing the test on a pin-on-disc tribo tester as per the ASTM G99 standard under dry sliding conditions. Tribological results indicate that hybridization of abaca and glass fiber into an epoxy matrix enhances the wear properties significantly. Maximum wear resistance is observed with AGGA-layered hybrid composite. The reduction in volumetric wear of AGGA composite is found to be lower than neat epoxy by 86.51%. However, the frictional force of AGGA composite increased by 54.17%. Furthermore, the morphology of fractured and worn-out surfaces is studied using a scanning electron microscope. It is inferred that failure is mainly due to the development of micro-cracks on both fiber and matrix, combined with fiber fragmentation, plowing, and debonding.